Effects of Irrigation Volume and Saline Water On Maize Yield and Soil in Southern Italy†. (20th January 2016) - Leogrande, Rita; Vitti, Carolina; Lopedota, Ornella; Ventrella, Domenico; Montemurro, Francesco
Abstract: A field experiment was carried out in southern Italy to investigate the effects of irrigation and salinity on a maize crop and soil properties. The experiment was laid out comparing different irrigation rates (I1, I2, I3—re‐establishing 50, 75 and 100% of the calculated maximum evapotranspiration) and water quality (FW, fresh water and SW, saline water). Grain yield was significantly greater by 60% in 2008 than in 2010. No significant difference was shown for grain yield between the irrigation treatments, whereas water productivity decreased significantly with increasing irrigation rates. Irrigation with saline water did not significantly reduce grain yield compared with fresh water, but it improved grain quality with higher protein content (9.1%) and lower grain moisture percentage (13.3%). Saline water determined a significant increase of saturated soil paste extract Na, ECe, SAR, some exchangeable cations and ESP compared with FW in both years. Furthermore, at the end of the experiment these parameters were lower than those at the end of the first maize crop. Lastly, in the saline treatment, at the end of the trial, the ECe and ESP values were below the critical threshold for soil salinization and/or sodification. Copyright © 2016 John Wiley & Sons, Ltd.